Synthesis and Characterization of Mixed Ligand Complexes of Thorium(IV) and Dioxouranium(VI) with Schiff Base of p-Anisidine and Dimethyl Sulphoxide - Rajendran, G.; Kala Kumari, C.R. (Asian Journal of Chemistry, 2010)
A series of six mixed ligand complexes of the actinide metal ions, viz., Th(IV) and UO2(VI) with a Schiff base of p-anisidine and dimethyl sulphoxide and various anions such as acetate, nitrate, sulpbate and thiocyanate have been synthesized and characterized. The analytical data include elemental analysis, molecular weight determinations, conductivity, spectral and thermal studies. The composition of these complexes are [Th(DMDA)4(DMSO)2(a)4], [Th(DMDA)4(DMSO)2(aa)2], [UO2(DMDA)2(DMSO)2(a)2] and [UO2(DMDA)2(DMSO)2(aa)], Where DMDA = 4,4' -dimethyl diphenyl azomethine, a = monovalent anion such as acetate, nitrate and thiocyanate and aa = divalent' anion such as sulphate. In these complexes schiff base of p-anisidine acts as a neutral monodentate ligand, DMSO and monovalent anion acts as unidentate ligand and divalent sulphate ion acts as a bidentate ligand.